Women's work : how culinary cultures shaped modern Spain - Ingram, Rebecca, 1977- (Nashville, Tennessee : Vanderbilt University Press, 2022)
"A study of cooking as it relates to Spanish modernity and the roles of Spanish women"--
Emilia Pardo Bazán : culinary nationalist and ambivalent feminist -- Frivolous and feminist : Carmen de Burgos's culinary-political platform -- Mythologies of culinary modernity : Gregorio Marañón and Nicolasa Pradera -- Cooking and civic virtue : women, work, and Barcelona. -- Conclusion: Feminist food studies and Spain
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
JSTOR
Keywords: Food habits -- Spain; Cooking -- Spain -- History; Women -- Spain -- Social conditions -- History; Social role -- Spain -- History; Feminism -- Spain; Spain -- Social life and customs; Women -- Spain -- Social conditions; Féminisme -- Espagne; Rôle social -- Espagne -- Histoire; Femmes -- Espagne -- Conditions sociales; Habitudes alimentaires -- Espagne; Espagne -- Mœurs et coutumes; COOKING / History; Cooking; Feminism; Food habits; Manners and customs; Social role; Women -- Social conditions; Spain; Electronic books; History; Literary criticism; Critiques littéraires.